Economic Interdependence of Indonesia in Global Value Chain: An Analysis of Multiregional Input-Output - Dwi Ervinda, Moch Yasin; Ariutama, I Gede Agus (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
Indonesia’s resilience to economic crises originating from the outside was due to the high domestic consumption as the main support for the economy. On the other hand, Indonesia does not have a significant role in the global value chain because of the low amount of export value and low product competitiveness. Using Multiregional Input-Output (MRIO) analysis, this study aims to map the interdependence and role of Indonesia in trade relations with major partner countries and see the magnitude of the economic influence of other countries on the domestic economy. The data used is the 35 economic sector MRIO tables issued by the Asian Development Bank in 2008 and 2018 consisting of 63 countries. The results indicate that Indonesia has low linkages in international trade with major partners. In addition, most of Indonesia's export commodities are intermediate goods that have low value-added. Furthermore, the simulation conducted in the study outlines that Indonesia is increasingly unaffected by the GDP changes of trading partner countries.